Benthic marine ecological shifts and carbonate diagenetic effects surrounding the end-Permian and end-Triassic mass extinctions - Greene, Sarah Elizabeth (University of Southern California Digital Library (USC.DL), 2015)
The Early-Mid Mesozoic was a time of broad ecological and geochemical change punctuated by two major biotic and environmental crises - the end-Permian and end-Triassic mass extinctions. In the wake of the end-Permian mass extinction, the Modern Fauna emerged as the dominant taxonomic group. Herein, bioclastic accumulations are used to track ecological dominance across the Early Mesozoic, particularly in the Middle Triassic aftermath of the end-Permian mass extinction interval. Additionally, a literature search is used to trace the waning ecological importance of the crinoids, constituents of the Paleozoic Fauna, through the Mesozoic. Despite diminished diversity, the Paleozoic Fauna regained ecological dominance in the post-extinction world. After a Middle Triassic comeback, the crinoids persisted as ecological dominants through the Jurassic before their ecological twilight in the earliest Cretaceous. The timing of these patterns does not fit the suggestion of an ecological upheaval caused by the end-Permian mass extinction, but rather points to other potential factors such as the Mesozoic Marine Revolution. ❧ The Triassic-Jurassic (T-J) boundary saw the rapid emplacement of a large igneous province resulting in a major carbon cycle perturbation, perhaps even inducing ocean acidification. The T-J boundary interval is used as a case study to explore how to identify ocean acidification in deep time. Thus far, the T-J boundary record is consistent with an acidification scenario. Fieldwork at multiple, geographically disparate boundary intervals shows an abundance of early diagenetic carbonate. In particular, unusual layers of aragonite fans which grew just below the sediment-water interface are identified globally. Abundant early diagenetic carbonate suggests that the sub-seafloor may have been a locus of carbonate precipitation across the T-J boundary interval and that the early diagenetic realm is a carbonate sink of unknown size and variability.